Perceptions of the first family physicians to adopt advanced access in the province of Quebec, Canada. (8th September 2016) - Breton, Mylaine; Maillet, Lara; Paré, Isabelle; Abou Malham, Sabina; Touati, Nassera
Abstract: In Quebec, several primary care physicians have made the transition to the advanced access model to address the crisis of limited access to primary care. The objectives are to describe the implementation of the advanced access model, as perceived by the first family physicians; to analyze the factors influencing the implementation of its principles; and to document the physicians' perceptions of its effects on their practice, colleagues and patients. Qualitative methods were used to explore, through semi‐structured interviews, the experiences of 21 family physicians who had made the transition to advanced access. Of the 21 physicians, 16 succeeded in adopting all five advanced access principles to varying degrees. Core implementation issues revolved around the dynamics of collaboration between physicians, nurses and other colleagues. Secretaries' functions, in particular, had to be expanded. Facilitating factors were mainly related to the physicians' leadership and the professional resources available in the organizations. Impediments related to resource availability and team functioning were also encountered. This is the first exploratory study to examine the factors influencing the adoption of the advanced access model conducted with early‐adopter family physicians. The lessons drawn will inform discussions on scaling up to other settings experiencing the same problems. Copyright © 2016 John Wiley & Sons, Ltd.